2018
DOI: 10.1093/jamia/ocy081
|View full text |Cite
|
Sign up to set email alerts
|

Reining in the QTc: reducing the risk of Torsades de Pointes across a major health system

Abstract: Hospitalized patients have a high prevalence of prolonged QTc and are a high-risk population for Torsades de Pointes (TdP). One modifiable risk factor for TdP is the use of QT prolonging drugs. Electronically alerting providers who are ordering QT prolonging drugs in at-risk patients may help to achieve safer prescribing practices. Our previous study decreased inappropriate prescription of IV haloperidol by 36% using a targeted "smart" electronic alert. We wanted to assess an approach to expanding this type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…20 This idea has prompted several centers to implement CDS systems to guide providers. In addition to the CDS program, here at the University of Colorado, 11,12 other investigators [21][22][23] have examined automated CDS at their respective institutions for impact on prescription patterns and outcomes. Bertsche et al examined a computerized CDS for drug-drug interactions in the ICU, and found that the CDS tool reduced incidence of QT prolongation by 64%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 This idea has prompted several centers to implement CDS systems to guide providers. In addition to the CDS program, here at the University of Colorado, 11,12 other investigators [21][22][23] have examined automated CDS at their respective institutions for impact on prescription patterns and outcomes. Bertsche et al examined a computerized CDS for drug-drug interactions in the ICU, and found that the CDS tool reduced incidence of QT prolongation by 64%.…”
Section: Discussionmentioning
confidence: 99%
“…500 ms). 11,12 These CDS tools decreased use of QT-prolonging medications broadly within the population. However, further work is needed to understand the strengths and weaknesses of this alert at the scale in which it is being applied and to identify measures to optimize its effectiveness.…”
Section: Background and Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Drug-induced long-QT syndrome (diLQTS) [1,2] is a major concern for inpatients worldwide and has been identified as a key target for clinical decision support tools [3][4][5][6][7]. Importantly, although certain medications have been implicated as having significant clinical risk [8,9], for others, despite a known risk of diLQTS, clinical validation has been lacking [10][11][12].…”
Section: Introductionmentioning
confidence: 99%